The role of owner in capital structure decisions: An analysis of single-owner corporations - James Ang; Rebel Cole; Daniel Lawson (The Journal of Entrepreneurial Finance (JEF), 2010)
This study examines the extent to which individual demographic characteristics of owners influence capital structure decisions. Using the Federal Reserve's 2003 Survey of Small Business Finances, we estimate the joint effects of traditional capital structure determinants and manager age, gender, education, business experience, sophistication, and wealth on the capital structure of single-owner corporations. By calculating the marginal contribution of personal risk tolerance, we demonstrate that owner preference contributes meaningfully to the explained variation in capital structure decisions.
Keywords: 650